2014
DOI: 10.15171/jcvtr.2014.004
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Predicts Declining of Circulating Proangiogenic Mononuclear Progenitor Cells in Chronic Heart Failure Patients

Abstract: Introduction: Serum uric acid (SUA) is considered a marker for natural progression of chronic heart failure (CHF) mediated cardiovascular remodelling. CHF associates with declining of circulating mononuclear progenitor cells (MPCs). The objective of this study was to evaluate the interrelationship between SUA concentrations and proangiogenic MPCs in ischemic CHF patients. Methods: The study population was structured retrospectively after determining the coronary artery disease (CAD) by contrast-enhanced spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Although CD34 + MPC populations are not associated with cardiac and vasculature remodelling or prognosis in CHF patients [36] , recent evidence suggests levels of circulating proangiogenic MPCs labelled CD14 + CD309 + and CD14 + CD309 + Tie 2+ cells were decreased in stable CHF patients [37] . In fact, a sufficient negative association of proangiogenic MPC level with SUA in CHF patients was found [35] . Arguing against a pure protective role of SUA in cardiovascular disease [38] , it was found the levels of SUA remained independently associated with lowed proangiogenic MPCs after adjusting for parameters with known impact on concentrations of MPCs.…”
Section: Circulating Mononuclear Progenitor Cells In Heart Failurementioning
confidence: 95%
See 1 more Smart Citation
“…Although CD34 + MPC populations are not associated with cardiac and vasculature remodelling or prognosis in CHF patients [36] , recent evidence suggests levels of circulating proangiogenic MPCs labelled CD14 + CD309 + and CD14 + CD309 + Tie 2+ cells were decreased in stable CHF patients [37] . In fact, a sufficient negative association of proangiogenic MPC level with SUA in CHF patients was found [35] . Arguing against a pure protective role of SUA in cardiovascular disease [38] , it was found the levels of SUA remained independently associated with lowed proangiogenic MPCs after adjusting for parameters with known impact on concentrations of MPCs.…”
Section: Circulating Mononuclear Progenitor Cells In Heart Failurementioning
confidence: 95%
“…Recent studies have demonstrated that circulating MPCs are declined progressively depending severity of CHF [32][33][34] . However, ih has been postulated that depletion of MPC numerous in circulation may link SUA with inflammatory response and outcomes in CHF [35] . Although CD34 + MPC populations are not associated with cardiac and vasculature remodelling or prognosis in CHF patients [36] , recent evidence suggests levels of circulating proangiogenic MPCs labelled CD14 + CD309 + and CD14 + CD309 + Tie 2+ cells were decreased in stable CHF patients [37] .…”
Section: Circulating Mononuclear Progenitor Cells In Heart Failurementioning
confidence: 99%
“…As an evidence of the opinion it has been allowed presenting data, which confi rm higher predictive value of elevated SUA in HF patients beyond etiology of disease, cardiac pump function, traditional risk factors and estimated glomerular fi ltration rate [24][25][26]. Interestingly, large numbers of clinical and observational studies have shown that elevated SUA levels are associated with reduced survival in in-patients and outpatients with several phenotypes of chronic HF, as well as in acute / actually decompensated HF [27][28][29].…”
Section: Short Communicationmentioning
confidence: 99%
“…Finally, co-acting endothelial injury, incompetence in vascular reparation mechanisms and existing co-morbidities (i.e. hypertension, obesity, hyperuricemia, dyslipidemia) may lead to endothelial dysfunction, acceleration of atherosclerosis, senescence, thereby they may negatively influence on CV risk and development of CV disease [11][12][13]. The key role in the endothelial repair, vasculogenesis, neovascularization and attenuation of vasculature function plays endothelial progenitor cells (EPCs) derived from bone marrow and peripheral blood [14].…”
Section: Introductionmentioning
confidence: 99%